Brain drain: Let's value, celebrate our talents - Abd Razak, Dzulkifli (2005)
NEWS that some Malaysian medical students on public scholarships had "turned their backs on the country" was not as shocking to the medical fraternity as it was to taxpayers. The exodus of doctors and other professionals from Malaysia is not a new phenomenon. This is an example of "brain drain" that the country has been suffering over the years. This only shows what impact heightened mobility and the demand for kworkers have on nations today, and is not unique to Malaysia. There is sharp concern that this is threatening socioeconomic growth in the developing world. Nowhere is this more apparent than among healthcare workers, notably doctors. Developed countries attract them directly or indirectly. For example, the various scholarships funded by the British Foreign and Commonwealth Office reportedly benefit more than 2,000 students a year, from close to 150 countries